Genome assembly at chromosome scale with telomere ends for Pearlspot, Etroplus suratensis - Vinaya Kumar Katneni; Karthic Krishnan; Sudheesh K Prabhudas; Roja Jayaraman; Nida Quraishi; Kumaraguru Vasagam; Ashok Kumar Jangam; Jesudhas Raymond Jani Angel; Nimisha Kaikkolante; Kumaravel Jayaraman; S Shekhar Mudagandur (Scientific Data)
Abstract The pearlspot, Etroplus suratensis is a climate resilient cichlid fish that exhibits unusual adaptation to salinity. The fish is able to complete full life cycle in diverse salinity habitats ranging from fresh water to marine environments. High-quality primary and phased genome assemblies were generated for pearlspot fish using PacBio HiFi and Arima HiC sequencing technologies, for the first time. The primary assembly is highly contiguous with contig N50 length of 36 Mb. The final assembly is of 1.247 Gb with N50 length of 51.57 Mb and 98% of the genome length anchored to 24 chromosomes. The genome was assessed to be 99.9% complete based on BUSCO evaluation and was predicted to contain 52.96% repeat elements. We have predicted 27,192 protein encoding genes, of which 21,580 were functionally annotated. The genome offers an invaluable resource to understand adaptation of pearlspot fish to diverse salinity habitats.